The Effect of Reduction Mammaplasty on the Vertebral Column: A Radiologic Study - Onder Karaaslan; H. Gokhan Demirkiran; Ozlem Silistreli; Erhan Sonmez; Yagmur Kaan Bedir; Melih Can; Gorkem Caliskan; Cem Aslan; Meltem Ayhan Oral; Yuksel Kankaya (The Scientific World Journal)
Some studies emphasized that anatomic mechanisms of vertebral aberrations could be associated with large breasts. The effect of mammaplasty operation on the vertebral column and body posture seems to be beneficial; in this trial, it was planned to investigate the objective radiologic effect of reduction mammaplasty on the posture of the vertebral column in a group of patients operated due to the large breasts. Thirty-four white women with large breasts were enrolled in this study. The patients were divided into three groups according to their breast cup sizes. Anteroposterior and lateral radiographs of the lumbosacral and thoracic spine were taken at baseline preoperatively, and the same radiographic images were taken in an average of 12 months later than the reduction mammaplasty operation. All were evaluated and compared for thoracic kyphosis angle and lumbar lordosis angle both preoperatively and postoperatively. The mean thoracic kyphosis angle was 40,53 preoperatively and 39,38 postoperatively. However, there was no statistically significant difference between the preoperative and postoperative measurements in all groups (P>0,05). The mean lumbar lordosis angle was 54,71 preoperatively and 53,18 postoperatively. Regarding the preoperative and postoperative measurements of lumbar lordosis angles, no statistically significant difference was found between the groups (P>0,05). Although breast size may be an important factor that affects body posture, reduction mammaplasty operations have little or no radiologic effect on the vertebral column.